2001
DOI: 10.1002/mrc.970
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and magnetic susceptibility effects on the MAS NMR linewidth of a tetrapeptide bound to different resins

Abstract: Under magic angle spinning, the NMR spectrum of the tetrapeptide Ala-Ile-Gly-Met bound to a Wang resin, and swollen in DMF, exhibits proton and carbon linewidths that are sharp enough to allow the complete characterization of the peptide using classical liquid-state NMR methods. The proton linewidths of the bound peptide remain, however, about three times larger than those of the free peptide in solution. The residual NMR linewidth originates essentially from incompletely averaged magnetic susceptibility effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…This technique results in averaging of the anisotropy of dipolar, quadrupolar, and chemical shift interactions (11, 45, 47, 74 -76). MAS solid-state NMR spectroscopy has been used, for example, during the investigation of peptides that are coupled to the resins used during solid-phase peptide synthesis (77)(78)(79). MAS results in well-resolved NMR spectra in which the heterogeneity of the sample determines to a large extent the half-width of the NMR resonances.…”
Section: Mas and Magic Angle-oriented Sample Spinning Solid-state Nmrmentioning
confidence: 99%
“…This technique results in averaging of the anisotropy of dipolar, quadrupolar, and chemical shift interactions (11, 45, 47, 74 -76). MAS solid-state NMR spectroscopy has been used, for example, during the investigation of peptides that are coupled to the resins used during solid-phase peptide synthesis (77)(78)(79). MAS results in well-resolved NMR spectra in which the heterogeneity of the sample determines to a large extent the half-width of the NMR resonances.…”
Section: Mas and Magic Angle-oriented Sample Spinning Solid-state Nmrmentioning
confidence: 99%
“…17,18 The presence of anisotropic susceptibility has been clearly shown in cases in which aromatic moieties are abundant in the medium, as in some resins used for solid-phase organing synthesis (SPOS). 4,19 The magnitude of the susceptibility broadening naturally increases linearly with the magnetic field size, a point that should not be forgotten when designing HRMAS experiments at high field, and variable field experiment actually demonstrated that this mechanism may be the dominant one behind residual line broadening in HRMAS. 19 Further enhancement of the resolution can be achieved though partial compensation for line distortions, which in MAS can be achieved by magnetic field compensation coils (shims), as in regular nonspinning or parallel spinning NMR.…”
Section: Hrmas: Susceptibility Broadening and Achievable Resolutionmentioning
confidence: 99%
“…4,19 The magnitude of the susceptibility broadening naturally increases linearly with the magnetic field size, a point that should not be forgotten when designing HRMAS experiments at high field, and variable field experiment actually demonstrated that this mechanism may be the dominant one behind residual line broadening in HRMAS. 19 Further enhancement of the resolution can be achieved though partial compensation for line distortions, which in MAS can be achieved by magnetic field compensation coils (shims), as in regular nonspinning or parallel spinning NMR. However, the field corrections should be now performed considering the spinning axis as the principal (quantization) direction.…”
Section: Hrmas: Susceptibility Broadening and Achievable Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…High resolution magic angle spinning (HRMAS) (1, 2) is a powerful tool for the characterization of molecules bound to swollen resins (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), swollen polymers (15), or other soft materials such as lipid membranes (16,17 ), biological tissues (18,19), or fluids contained in solid media (20). The linewidth observed in the static 1 H NMR spectra of such samples originates mainly from large variations in the bulk magnetic susceptibility of the sample (14,21).…”
Section: Introductionmentioning
confidence: 99%